2014
DOI: 10.1590/s0104-66322014000100007
|View full text |Cite
|
Sign up to set email alerts
|

Non-woven nanofiber chitosan/peo membranes obtained by electrospinning

Abstract: -The present work focused on the preparation and morphological characterization of chitosan-based nanofiber membranes, aiming at applications in medical and pharmacological areas. Membranes with nanofiber diameters ranging from 50 -300 nm were prepared from polymer solutions through the electrospinning process. To stabilize the process, it was necessary to use poly(ethylene oxide) (PEO), which is a biocompatible synthetic polymer. Pure chitosan solutions, as well as chitosan and PEO solution blends, were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 19 publications
3
18
0
Order By: Relevance
“…The composition of the membranes consisted of 80% chitosan and 20% poly(oxyethylene) (PEO). Those membranes were obtained through the electrospinning process using chitosan (Sigma-Aldrich) of medium molecular weight with 80% deacetylation level and 284 cps viscosity at 1% PA-ACS glacial acetic acid (Synth) and poly(oxyethylene) solution with 900,000g/mol molecular weight (Sigma-Aldrich) (Bizarria et al, 2014). The average diameter of the fibers obtained corresponded to 100 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The composition of the membranes consisted of 80% chitosan and 20% poly(oxyethylene) (PEO). Those membranes were obtained through the electrospinning process using chitosan (Sigma-Aldrich) of medium molecular weight with 80% deacetylation level and 284 cps viscosity at 1% PA-ACS glacial acetic acid (Synth) and poly(oxyethylene) solution with 900,000g/mol molecular weight (Sigma-Aldrich) (Bizarria et al, 2014). The average diameter of the fibers obtained corresponded to 100 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The parameters to be controlled in that process refer to the equipment, i.e., the applied voltage, types of collectors, tip to collector distance and feed rate; the ambient parameters (temperature and relative humidity); and finally the solution parameters, such as viscosity, conductivity and surface tension (Bhardwaj and Kundu, 2010). Countless researchers have reported the relationship between these parameters and the spinnability of several polymers (Fong et al 1999;Mit-Uppatham et al, 2004;Okutan et al, 2014, Bizarria et al, 2014. Regarding the solution parameters, they are not only influenced by concentration and composition, but also by the polymer properties, mainly molecular weight and ion formation in the solution.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, our research group has been dedicated to the study of nanostructured biopolymer Silver nanoparticles incorporated into nanostructured biopolymer membranes produced by electrospinning 913 membranes for application in the medical and dental fields (Nista et al, 2012;Nista et al, 2013;Nista, Bettini, Mei, 2015;Bizarria, Davila, Mei, 2014;Kleinubing et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that an especially lucrative opportunity lies in applying these polymeric nanostructures in the medical field (Abdelgawada, Hudsona, Rojas, 2014;Chaloupka, Malam, Seifalian, 2010;Dallas, Sharma, Zboril, 2011). The literature contains a great deal of studies demonstrating the successful application of these nanostructures in the healthcare, pharmaceutical and cosmetic industries for repairing and regenerating the skin and organs; as drug delivery vectors and therapies; biocompatible and biodegradable implants; in medical diagnosis and instrumentation; as tissue protective agents that guard against infection; and in cosmetics, molecular medicines, supplements and body care applications in the field of dentistry (Nista, Bettini;Mei, 2015;Bizarria, Davila, Mei, 2014;Kleinubing et al, 2014).The AgNPs possess superior antimicrobial properties compared to other salts, due to their extremely large surface area, which provides better contact with microorganisms (Rai, Yadav, Gade 2009). Although the mechanism of action of silver nanoparticles on microorganisms is not fully understood, there are hypotheses that these nanoparticles can cause cell lysis or inhibit cell transduction (Prabhu, Poulose, 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation